Smokescreen - Johansen, Iris; Rodgers, Elisabeth S. (New York, NY : Hachette Audio, 2019)
Forensic sculptor Eve Duncan journeys to Africa to help families torn apart by a violent attack deep in the jungle, but she may be putting herself in more danger than she knows.
Keywords: Duncan, Eve (Fictitious character) -- Fiction; Facial reconstruction (Anthropology) -- Fiction; Women sculptors -- Fiction; Guerrillas -- Fiction; Africa -- Fiction; Thrillers (Fiction); Detective and mystery fiction; Audiobooks